Dampak Ekonomi Digital Terhadap Pertumbuhan Ekonomi Masyarakat Di Daerah Tertinggal - Giawa, Man Saro Kasih (Jurnal Ilmu Ekonomi dan Bisnis, 2026)
The digital economy offers significant opportunities to address economic disparities in underdeveloped regions by improving market access and transaction efficiency. This study aims to analyze how the adoption of digital technology affects income and economic growth in areas with limited infrastructure. Using qualitative methods, including literature review and secondary data analysis, the study found that digitalization through e-commerce and digital finance platforms has positively contributed to expanding the reach of local products. However, its effectiveness is highly dependent on the availability of internet infrastructure and the level of digital literacy in the local community.